Minimum risk estimation of scale parameter of length biased Maxwell distribution with censoring - Singh, Kusum Lata; Srivastava, R. S. (IJRDO -JOURNAL OF MATHEMATICS, 2017)
Length biased distribution arise when the probability of inclusion of population unit in sample is related to the value of the variable measured. For example textile sampling Cox (1969). In this paper the genesis of a length biased Maxwell distribution has been given. The minimum risk estimators of its scale have been obtained under squared error, precautionary and other two loss functions with the help of a type II censored sample. The relative efficiencies have been calculated for the sake of comparison.